KEBERSIHAN LINGKUNGAN DAN KAITANNYA TERHADAP PENINGKATAN PENDAPATAN KELUARGA DESA OMBE BARU KECAMATAN KEDIRI KABUPATEN LOMBOK BARAT - Netrawati , I Gusti Ayu Oka; Nuada, I Wayan; Permadi, I Gusti Agung Didit Eka; Asari, Hasim Al; Masyoung, Ramdani Iqbal (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
To improve the quality of the environment, knowledge environment has a role urgent in guarding a sustainable environment, because through knowledge man more understanding and awareness will danger waste House ladder to the environment, especially danger pollution to health human. Income family is all form returns obtained as reward or reply service on donation somebody to the production process. Income family could be sourced from, effort owned (self-employed), working to others, and results from property (asset). Mother House ladder, farmer, and trader do not want to make goods results cycle repeat rubbish plastic in his efforts make it as goods useful new and worth plus in a manner economy but because they no knowing what that mark plus economy and processing rubbish plastic as well as what benefit for enhancement income their family gets this seen from enthusiastic they moment activity devotion to Public going on, even at the end activity all participant convey accept love because has taught about processing waste rubbish plastic becomes goods useful new and worth high economical and hope they keep going accompanied as well as permanent stage activity like this.